Project-Based Writing Instruction in EFL Contexts: A Critical Narrative Literature Review - Kalayo Hasibuan; Aufa Khairunnisa; Mela Novianti (ANTHOR: Education and Learning Journal, 2026)
Increasing demand for effective writing instruction in English as a Foreign Language (EFL) classrooms has encouraged educators to explore more student-centered learning approaches. One of the approaches that has received growing attention is Project-Based Writing Instruction (PBWI), which integrates writing activities with collaborative and meaningful projects. This article presents a critical narrative literature review that examines the implementation of PBWI in various EFL contexts. The review focuses on studies published between 2018 and 2026 obtained from Google Scholar, DOAJ, ERIC, and Scopus-indexed journals. The findings indicate that PBWI contributes positively to students’ writing development, particularly in terms of idea organization, vocabulary use, creativity, and learner engagement. In addition, project-based activities encourage collaboration, critical thinking, and greater student participation during the writing process. However, several studies also report challenges related to time management, classroom heterogeneity, limited technological resources, and teachers’ readiness in managing project-oriented instruction. Overall, the literature suggests that PBWI offers meaningful opportunities for improving writing instruction in EFL classrooms when supported by appropriate pedagogical planning and contextual adaptation.